Pelatihan Produksi Sabun Cair dari Crude Palm Oil (CPO) di Desa Jilatan Kabupaten Tanah Laut Dalam Rangka Pencegahan Covid 19 - Susi Susi; Arief Rahmad Maulana Akbar; Rini Hustiany; Tanwirul Millati; Alan Dwi Wibowo; Dessy Maulidya Maharani; Agung Cahyo Legowo (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2022)
Prevention of the COVID-19 virus can be done by regularly washing hands or using hand sanitizer. This step can prevent the COVID-19 virus from sticking to the surface of the skin.. Therefore, the availability of hand washing soap is urgent as an initial step for corona prevention. The availability of hand soap can be provided independently in the community because the liquid laundry soap can be processed with palm oil. It can be an opportunity for the palm oil community to produce and fulfill the needs community. Handling problems by the community in the era of the covid 19 pandemic are related to understanding and insight for preventing Covid 19 from the family environment, one of which is the awareness of washing hands as often as possible using soap. Therefore, knowledge of producing crude palm oil-based liquid soap in communities around oil palm plantations as well as knowledge of the role of palm-based liquid soap for sanitation and entrepreneurial opportunities are good. This community service activity was conducted through counseling and training related to the manufacture of crude palm oil-based liquid soap for the community of oil palm farmers around the Cipta Prima Sejahtera Professional Services Cooperative in Jilatan Village, Tanah Laut Regency. The activity was to provide knowledge about palm oil and liquid soap-based palm oil that are easy to prepare. During the Covid 19 period, hand washing activities are important as a preventive measure, so the availability of liquid soap independently needs to be produced. The evaluation showed that the training participants were very satisfied with this training, gave a very good response regarding the usefulness and sustainability of this community service activity, and hoped that it could be followed up regarding business sustainability.